Identification of potential biomarkers of cardiotoxicity induced by doxorubicin therapy in a tumour bearing model by targeting specific micro-RNAs - Ogundipe, Temitope Richard (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.